2018
DOI: 10.1007/s00360-018-1169-y
|View full text |Cite
|
Sign up to set email alerts
|

Physiological protective action of dissolved organic carbon on ion regulation and nitrogenous waste excretion of zebrafish (Danio rerio) exposed to low pH in ion-poor water

Abstract: Dissolved organic carbon (DOC) represents a heterogeneous group of naturally-occurring molecules in aquatic environments, and recent studies have evidenced that optically dark DOCs can exert some positive effects on ionoregulatory homeostasis of aquatic organisms in acidic waters. We investigated the effects of Luther Marsh DOC, a dark allochthonous DOC, on ion regulation and N-waste excretion of zebrafish acutely exposed to either neutral or low pH in ion-poor water. In the first experiment, simultaneous expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 49 publications
1
20
2
Order By: Relevance
“…Interestingly, in that study, increases in ammonia net fluxes were facilitated in reference water by the addition of Ca 2+ , demonstrating that native DOC molecules may interact with gill membranes in the same manner as Ca 2+ ions with respect to ammonia excretion mechanisms (Wood et al ., ). In D. rerio , a stimulation in J Amm.net was seen in fish exposed to pH 4.0 in IPW in the presence of two different sources of DOC, which was thought to be essential for animals to keep Na + uptake coupled to ammonia excretion under acidic conditions (Duarte et al ., , ). This coupling was thought to be associated with an upregulation of the Rh‐protein–Na + –NH 4 + exchange metabolon in the gills (Weihrauch et al ., ; Wright & Wood, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in that study, increases in ammonia net fluxes were facilitated in reference water by the addition of Ca 2+ , demonstrating that native DOC molecules may interact with gill membranes in the same manner as Ca 2+ ions with respect to ammonia excretion mechanisms (Wood et al ., ). In D. rerio , a stimulation in J Amm.net was seen in fish exposed to pH 4.0 in IPW in the presence of two different sources of DOC, which was thought to be essential for animals to keep Na + uptake coupled to ammonia excretion under acidic conditions (Duarte et al ., , ). This coupling was thought to be associated with an upregulation of the Rh‐protein–Na + –NH 4 + exchange metabolon in the gills (Weihrauch et al ., ; Wright & Wood, ).…”
Section: Discussionmentioning
confidence: 99%
“…ions with respect to ammonia excretion mechanisms (Wood et al, 2003). In D. rerio, a stimulation in J Amm.net was seen in fish exposed to pH 4.0 in IPW in the presence of two different sources of DOC, which was thought to be essential for animals to keep Na + uptake coupled to ammonia excretion under acidic conditions (Duarte et al, 2016(Duarte et al, , 2018. This coupling was thought to be associated with an upregulation of the Rh-protein-Na + -NH 4 + exchange metabolon in the gills (Weihrauch et al, 2009;Wright & Wood, 2009).…”
Section: Ammonia Excretion Plasma Ammonia and Urea Concentrations mentioning
confidence: 99%
“…With respect to paracellular junctions, the presence of DOC (6–15.5 mg/L) has been shown to reduce the efflux rates of Na + and Cl − across the gills in a variety of species, both at circumneutral and acidic pHs, but often with more pronounced effects in the latter (Al‐Reasi et al, 2016; Duarte et al, 2016, 2018; Gonzalez et al, 2002, 2006; Wood et al, 2002, 2003). In freshwater stingrays, the protective effects of the natural DOC of Rio Negro blackwater at pH 4.0 were mimicked by a 10‐fold increase in environmental Ca 2+ concentration (in the absence of DOC), suggesting that DOC had the same “tightening” actions on the paracellular junctions as those of Ca 2+ discussed earlier (Wood et al, 2003).…”
Section: The Protective and Supportive Effects Of Natural Doc On Ionoregulationmentioning
confidence: 99%
“…The dissociation of protons from allochthonous DOC is the major cause of acidity in peat bogs and many other natural blackwaters. However, there is now extensive evidence in freshwater fish that natural DOCs may actually mitigate the ionoregulatory disturbances of the ambient low pH which they help to create (Duarte et al, 2016, 2018; Gonzalez et al, 2002; Wood et al, 2003, 1998). It has even been suggested that DOCs may affect ventilation (Holland et al, 2014; Perry et al, 2021) and respiratory gas exchange (O 2 , CO 2 , and ammonia) at the gills (Matsuo et al, 2004), and at least for ammonia, there are data that support this (Duarte et al, 2016, 2018; Wood et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation